Utilization of Multiplication Board Learning Media to Improve Mathematics Learning Outcomes for Class 10 Students with Mental Retardation at SLB C Autism Negeri Kedungkandang - Widianti, Karrinia Sindy Ayu; Handayani, Zannuba Lutfia; Sari, Meitha Atika; Firdiana, Ade Dian; Hastuti, Wiwik Dwi (Proceedings Series of Educational Studies, 2024)
Learning mathematics is often a challenge for students at various levels of education, especially for mentally retarded students at SLB C Autism Negeri Kedungkandang. One topic that students often find difficult is multiplication. The cognitive limitations of students with intellectual disabilities make understanding abstract concepts such as multiplication more difficult, requiring more effective teaching methods. One innovation that can be implemented is the use of multiplication board learning media. This study aims to evaluate the effectiveness of the multiplication board in improving the mathematics learning outcomes of grade 10 students with intellectual disabilities. The methods used include observation, intervention, pretest and posttest, as well as interviews with teachers and students. The research results show that the use of a multiplication board can improve understanding of multiplication concepts, reduce errors in calculations, increase students' selfconfidence, and encourage active involvement in the learning process. The use of visual aids is effective in helping mentally retarded students understand and master multiplication operations. Of a total of 6 students, the results showed significant improvement after implementing the multiplication board, with 4 students able to do multiplication independently and 2 other students requiring less help than before. Keywords: Mental retardation; Instructional Media ; Mathematics ; Multiplication Board